MODIFIKASI MEDIA SPIRULINA PLATENSIS SEBAGAI UPAYA PEMANFAATAN AIR LIMBAH BUDIDAYA IKAN LELE - Hendro Widyantoro; Marini Wijayanti; Sefti Heza Dwinanti (Universitas Sriwijaya, 2018)
ABSTRACTThe purpose of this study was to determine the best fertilizer compotition that was made from technical fertilizer and waste water of cat fish farming. This experimental was conducted at Aquaculture Laboratory, Faculty of Agriculture, Sriwijaya University. It used complete randomized design (CRD) method which had five treatments and three replications, the waste water from catfish pond (P0), waste water from catfish pond + 25% technical fertilizer (P1), waste water from catfish pond + 50% technical fertilizers (P2), the waste water from catfish pond + 75% technical fertilizers (P3), the waste water from catfish pond + 100% technical fertilizers (P4). The results showed that the best maximum density of S. platensis was P3 about 3.98 g l-1, and growth rate was equal to 2.80% day-1. The most significant parameter of water quality was ammonia which decreased until 82.78%. Besides, it was more beneficial than others based on Return Cost Ratio (R/C ratio) and Benefit Cost Ratio (B/C ratio) which were 3.66 and 2.66 respectively. Keywords: Spirulina platensis, waste water pond of catfish, modified media